The PENGORGANISASIAN POSYANDU REMAJA SEBAGAI UPAYA UNTUK MENINGKATKAN PELAYANAN KESEHATAN REMAJA DI DESA CIJAGANG - Abigael, Putri; Esterilita , Mari; Kartikawati, Dewi (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2024)
Based on UNICEF data, Indonesia has the highest rate of early marriage in the world, including in Cijagang Village. On the issue of problems that occur, it is important to organize the Youth Posyandu as an effort to prevent early marriage, pre-marital sex and drug use in Cijagang Village. The purpose of establishing Posyandu Remaja is to improve access and health services for adolescents, increase knowledge about reproductive health and nutrition, and prevent juvenile delinquency. The method used was FGD with observation and interview techniques. The results show that the adolescent posyandu in the village has not been implemented due to limited medical equipment and lack of qualified cadres. Through the process of organizing and training, the management structure of the adolescent posyandu was formed. Interventions were conducted through training and socialization, where the results of the pre-test and post-test showed an increase in the knowledge and skills of posyandu cadres. The formation of the adolescent posyandu management was also successfully carried out with the issuance of an official decree. In conclusion, adolescent posyandu activities contribute to solutions to health problems and have a forum for communication for adolescents in Cijagang Village